Toward Classroom Experiences Inclusive of Students with Disabilities - Metatla, Oussama; Thieme, Anja; Brulé, Emeline; Bennett, Cynthia; Serrano, Marcos, Christophe Jouffrais (ACM Interactions Article, 2018)
More than ever, digital content and tools are being introduced and accepted in diverse educational contexts, offering opportunities for innovation and for making learning processes more encompassing, engaging, and collaborative. Multimodal tools fostering tactile, auditory, and spatial learning promise increased access for students with vision impairments (VI). Yet many existing popular classroom technologies, such as Scratch for learning computer programming, rely heavily on visual content and interactions. In practice, this means that students with VI continue to rely on screen readers, magnifiers, and braille displays to access and engage with educational materials, while also leveraging frequent support by a teaching assistant or the use of specialized tools. Although these are all important mechanisms to make educational content more accessible, they are inherently designed to be used by VI learners alone, often leaving the person isolated and excluded from learning activities with other students; meaning that accessible and assistive technology (AT) cannot alone foster connection among students with various abilities [1]. In this article, we outline three areas of research and debate that we identified during the CHI 2018 workshop on the design of inclusive educational classroom technology for people with VI [2]. These relate to opportunities and challenges for: i) inviting connection, ii) promoting people with VI as creative agents, and iii) developing effective assessments of educational technologies at scale. We unpack each of these three topics on which we reflected and shared during the workshop. We present them as the beginnings of a useful rubric to follow when planning inclusive education research. These tactics combine to push back against traditional educational settings for students with disabilities that isolate them. Instead, they intend to facilitate interdependencies among students by inviting connections and to maintain all participants as learners and contributors [3]. As such, they emphasize the participation of all students while attempting to uplift those with disabilities who have been traditionally marginalized [4].